The Role of Sleep in the Relationship Between ADHD Symptoms and Stop Signal Task Performance. Issue 13 (November 2021) - Mann, Brittany; Sciberras, Emma; He, Jason; Youssef, George; Anderson, Vicki; Silk, Timothy J.
Background: ADHD commonly occurs with sleep problems and secondary cognitive impairments such as inhibitory control. Sleep problems may explain attentional lapses and inhibition performance variability in children with ADHD. This study applied Bayesian analyses to examine the relationship between ADHD symptoms, sleep problems, and inhibition.Methods: Participants included 73 children with ADHD and 73 non-ADHD controls, aged 10.5 to 13.5 years. The Stop Signal Task measured inhibition. Sleep problems were measured with the Adolescent Sleep Wake Scale and parent-report.Results: ADHD symptoms are associated with sleep problems and reaction time variability, however, sleep problems accounted for more variance in inhibition performance than both hyperactive and inattentive symptoms.Conclusion: Sleep problems account for inhibition performance over and above ADHD symptom severity in children with and without ADHD diagnoses. This suggests clinical utility in assessing sleep in children with manifestations of ADHD, and interventions targeting sleep problems concurrently with behavioral symptoms. This further adds to the discussion on overdiagnosis of ADHD due to behavioral presentations of underlying sleep disorders. Treatment for phenotypes of ADHD could be enhanced by targeting sleep problems, in addition to inhibition deficits and attentional lapses.